PENGARUH PEMIKIRAN IBNU MADHA’ TENTANG USHUL AL-NAHWI AL-‘ARABI DALAM MEMAHAMI TEKS KEAGAMAAN - Faisol, M. (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2009)
”Nahwu” or sintax is a science born in the era of codification (Ashr al-Tadwin). In this field, there are many schools: Kufa, Bashrah, Baghdad, Egypt and Andalus. Each school has its own method and thought or what is called ushul al-nahwi (qiyas, ta’lil, ta’wil and amil). This research in included in the study of thought. The public figure of this research object is Ibnu Madha’, that is his ideas on ushul al-nahwi al-arabi and the implication in understanding divine texts. Ibnu Madha’ refused the concept of ushul al-nahwi al-arabi: qiyas, amil, ta’lil dan ta’wil, that have beeen made as the concept of mental interpretatif (al-Shurah al-Zhihniyyah al-Ta’wiliyyah) in lying the foundation of Arabic language. Ibnu Madha’ refusal to the ushul al-nahwi opens up the space of freedom for reason to express in order to obtain the meaning that is not stated literally in the text.